2016
DOI: 10.1037/xge0000182
|View full text |Cite
|
Sign up to set email alerts
|

Separate but correlated: The latent structure of space and mathematics across development.

Abstract: The relations among various spatial and mathematics skills were assessed in a cross-sectional study of 854 children from kindergarten, third, and sixth grades (i.e., 5 to 13 years of age). Children completed a battery of spatial mathematics tests and their scores were submitted to exploratory factor analyses both within and across domains. In the within domain analyses, all of the measures formed single factors at each age, suggesting consistent, unitary structures across this age range. Yet, as in previous wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
278
7
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(312 citation statements)
references
References 146 publications
(188 reference statements)
24
278
7
3
Order By: Relevance
“…Spatial skills may be more important for individuals at an earlier stage of learning than those in later stages (Uttal & Cohen, ). During initial learning, or for individuals with lower levels of domain‐specific knowledge, a learner may use spatial processing to establish mental maps and models, or to problem solve (Mix et al ., ). In line with this, for example, Hambrick et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Spatial skills may be more important for individuals at an earlier stage of learning than those in later stages (Uttal & Cohen, ). During initial learning, or for individuals with lower levels of domain‐specific knowledge, a learner may use spatial processing to establish mental maps and models, or to problem solve (Mix et al ., ). In line with this, for example, Hambrick et al .…”
Section: Introductionmentioning
confidence: 97%
“…In addition to often cited examples of scientific discoveries resulting from creative spatial thought, a growing body of research with adults and adolescents highlights a more specific link between spatial ability and various aspects of science learning (e.g., Kozhevnikov & Thornton, ). However, in contrast to the spatial ability and mathematics literature (e.g., Mix et al ., ), the relationship between spatial ability and science learning in younger children has been largely neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Mix et al . () found that mental rotation best predicted mathematics performance in younger students, while spatial visualization was the best predictor of performance by grade 6 (especially place value, word problems, and algebra concepts). Other studies have revealed strong associations between visuospatial ability and performance on number line tasks (e.g., Simms, Clayton, Cragg, Gilmore, & Johnson, ), even when expertise is accounted for (Sella, Sader, Lolliot, & Cohen Kadosh, ).…”
Section: Introductionmentioning
confidence: 98%
“…Other studies emphasized that mathematics is one of the concepts that is mentally represented in a spatial format [45,46]. Moreover, the study by [47] detailed specific mathematical tasks that predicts the most variance in the spatial ability of children aged 5 to 13.…”
Section: Discussion On Holzinger Resultsmentioning
confidence: 99%